The Promiscuous Profile of Complement Receptor 3 in Ligand Binding, Immune Modulation, and Pathophysiology - Lamers, Christina; Plüss, Carla Johanna; Ricklin, Daniel (Frontiers in Immunology, 2021)
The β2-integrin receptor family has a broad spectrum of physiological functions ranging from leukocyte adhesion, cell migration, activation, and communication to the phagocytic uptake of cells and particles. Among the members of this family, complement receptor 3 (CR3; CD11b/CD18, Mac-1, αMβ2) is particularly promiscuous in its functional profile and ligand selectivity. There are close to 100 reported structurally unrelated ligands for CR3, and while many ligands appear to cluster at the αMI domain, molecular details about binding modes remain largely elusive. The versatility of CR3 is reflected in its functional portfolio, which includes prominent roles in the removal of invaders and cell debris, induction of tolerance and synaptic pruning, and involvement in the pathogenesis of numerous autoimmune and chronic inflammatory pathologies. While CR3 is an interesting therapeutic target for immune modulation due to these known pathophysiological associations, drug development efforts are limited by concerns of potential interference with host defense functions and, most importantly, an insufficient molecular understanding of the interplay between ligand binding and functional impact. Here, we provide a systematic summary of the various interaction partners of CR3 with a focus on binding mechanisms and functional implications. We also discuss the roles of CR3 as an immune receptor in health and disease, as an activation marker in research and diagnostics, and as a therapeutic target.